Acupuncture for neuropathic pain: A meta-analysis of randomized control trials - Feng, Zitong; Cui, Shaoyang; Yang, Huijun; Wang, Yixiao; Zhou, Xuan; Wong, John; Lai, Liting; Yang, Zeyu; Huang, Bingjing; Zheng, Huiyan; Xu, Mingzhu (Frontiers in Neurology, 2023)
Background: Neuropathic pain (NP) is expected to increase due to the high risk of global population aging. Acupuncture has definite clinical effect on NP. Therefore, a systematic review and meta-analysis was conducted to evaluate the effect on pain intensity and safety of acupuncture in patients with NP. Methods: An encompassing search of specific authoritative databases in English, from their inception to May 2022, was performed. The databases were as follow: Scopus, Ovid EMBASE, Ovid Cochrane Database of Systematic Reviews, Ovid Cochrane Central Register of Controlled Trials, Ovid MEDLINE(R) and Epub Ahead of Print and In-Process & Other Non-Indexed Citations, and Daily. All the randomized controlled trials regarding acupuncture treatment of NP will be included. Methodological quality assessment of the included trials was assessed based on the risk of bias from Cochrane handbook. A meta-analysis was performed for the main outcomes. In addition, sensitivity analysis, subgroup analysis and funnel plot were also carried out. Results: A total of 16 studies with 1021 patients with NP were evaluated in systematic review. According to results of over-all meta-analysis in eight RCTs with 338 participants, the acupuncture group was better than the control group in improving changes in pain intensity (SMD -0.59, 95% CI -0.95 to -0.23, P=0.001). Eleven studies mentioned the safety conditions, of which induced by acupuncture which were mentioned above were mild and reversible. Both the sensitivity analysis and funnel plot analysis showed that the meta-analysis was stable and irreversible without publication bias. The GRADE was rated as "very low". Conclusion: The acupuncture group seemed worse than conventional treatments on changes in pain intensity, but there were benefits when compared to sham intervention or blank control in treating NP. The acupuncture induced adverse events were mild and reversible. However, the interpretation of our results should be performed cautiously due to low methodological quality.